A review on mechanical properties of SnAgCu/Cu joint using laser soldering - Nabila, Tamar Jaya; Siti Rabiatull Aisha, Idris; M., Ishak (Springer, Singapore, 2018)
This paper focuses on publishing the review of mechanical properties at the interface between SnAgCu (SAC) solder and Copper substrate after laser soldering. This involved on basic principles of solder alloy and Copper diffusion mechanism. In addition, this paper also reviews laser solder effects towards mechanical properties of the solder joint. This paper approach on the review of the solder joint strength which regards to intermetallic compound type and thickness. The output of this paper is to create an understanding for the readers about variance of laser soldering parameters and its effect on the mechanical properties of the solder joint by including discussion from other research paper findings.